Respon Dosen dan Mahasiswa Terhadap Penggunaan Media Pembelajaran Multimedia Interaktif Macromedia Flash - Dewi Hikmah Marisda; Rahmawati Rahmawati; Andi Arie Andriani (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2020)
This research is motivated by changes in the science learning process, especially at the tertiary level which trains student teacher candidates to use their thinking potential through social interaction in learning. In addition, the lack of development of the media in Integrated Science lectures is also a particular concern in this study. The purpose of this study is to analyze how the response of lectures and students of Physics Education at the University of Muhammadiyah Makassar to the use of Interactive Multimedia Macromedia Flash in Integrated Science lectures. The research sample consisted of 5 (five) integrated science lectures and 35 (thirty-five) students. This research is qualitative research that describes how the response of lecturers and students to the learning media used. The data in this research are lecturer response questionnaire data and student response questionnaire data. The data is then analyzed descriptively. Based on the results of the validation analysis of learning media by the validator (expert), the Aiken index average 0,76 in the medium category. Based on the results of the study found 87,50 % of lecturers responded positively to the use of interactive multimedia learning media with Macromedia Flash in Integrated Science lecturers. And as much as 83,86 % students gave a positive response to the use of interactive multimedia learning media with Macromedia flash in Integrated Science lectures